Scrotal abscess caused by actinomycosis turicensis: about an observation and literature review - Abi, Rachid; Tagajdid, Mohamed Reda; Janvier, Frederic; Bousquet, Aurore; Larréché, Sebastian; Mérens, Audrey (International Journal of Research in Medical Sciences, 2017)
Actinomyces turicensis, Gram positive bacillus, immovable and anaerobic, is a saprophytic of the human natural cavities. The scrotal actinomycosis caused by Actinomyces turicensis is a rare location; it was described once in literature by a patient within gangrene infection. Reported here is a case of scrotal abscess and Actinomyces turicensis. The slow growth of the Actinomyces turicensis represents a diagnostic difficulty in which its utility is to extend the culture during five days. The identification based on biochemical character with the APICoryne is not always easy to succeed, in which the interest of the mass spectrometry and/or of the molecular biology.